Time Management Styles and Work Performance of Public Secondary School Teachers in San Marcelino District Zambales - Jaballa, Jennelyn; Nening, Bernadette (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to assess the time management styles and work performance of public secondary school teachers in the San Marcelino District, Zambales. Methods and Materials: A descriptive-correlational research design was utilized, with survey questionnaires distributed to 144 public secondary school teachers in the San Marcelino District. The study used total population sampling. Teachers’ work performance was assessed through their Individual Performance Commitment and Review Form (IPCRF). Statistical analyses, including ANOVA and Pearson’s R correlation, were employed to determine the significance of relationships between time management styles and work performance. Findings: The study found that teachers scored high in keeping commitments, with a mean score of 3.73 (on a scale of 1-4), particularly excelling in punctuality during meetings (mean = 3.84). Control over interruptions received a lower composite mean of 2.67, indicating moderate effectiveness in this area. In planning, teachers scored a composite mean of 3.82, indicating strong planning skills. Resource utilization was another strong area, with a composite mean of 3.86. Teachers with higher levels of education (Master’s degree or higher) and those in higher positions demonstrated significantly better time management (p < 0.05). A positive correlation (r = .174, p = .037) was found between balancing lifestyle and basic content knowledge and pedagogy, showing that personal-professional balance improves performance. Conclusion: Effective time management, particularly in planning, resource utilization, and keeping commitments, significantly impacts teachers' work performance. Educational institutions should focus on time management training and promoting work-life balance to further enhance teacher performance.